(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This scientific thesis summarizes the experience of developing deposit operations in commercial banks of the United States, Japan, and Russia. The study examines issues such as the diversification of deposit products, the deposit insurance system, digital channels, deposit stability in a low-interest-rate environment, deposits in national currency, and flexible interest rate policy. Based on the generalized findings, proposals have been developed for commercial banks in Uzbekistan aimed at strengthening customer confidence, segmenting deposit products, expanding digital deposit services, and forming a stable resource base.